Kolumna szyjna kręgosłupa – ruchomość i wybrane sposoby jej pomiaru – przegląd literatury = Cervical vertebral column - mobility and selected ways of measurement - a literature review - Porzych, Piotr; Ratuszek-Sadowska, Dorota; Pyskir, Małgorzata; Simińska, Joanna; Ogurkowski, Karol; Kitschke, Ewa (Journal of Education, Health and Sport, 2016)
Porzych Piotr, Ratuszek-Sadowska Dorota, Pyskir Małgorzata, Simińska Joanna, Ogurkowski Karol, Kitschke Ewa. Kolumna szyjna kręgosłupa – ruchomość i wybrane sposoby jej pomiaru – przegląd literatury = Cervical vertebral column - mobility and selected ways of measurement - a literature review. Journal of Education, Health and Sport. 2016;6(6):505-516. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56384 http://ojs.ukw.edu.pl/index.php/johs/article/view/3638 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 25.06.2016. Kolumna szyjna kręgosłupa – ruchomość i wybrane sposoby jej pomiaru – przegląd literatury Cervical vertebral column - mobility and selected ways of measurement - a literature review Piotr Porzych, Dorota Ratuszek-Sadowska, Małgorzata Pyskir, Joanna Simińska, Karol Ogurkowski, Ewa Kitschke Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Kręgosłup szyjny to najbardziej mobilny odcinek całej kolumny kręgowej. Kręgi szyjne, tworząc szkielet szyi, wspierają głowę umożliwiając jej odpowiednią orientację w przestrzeni we wszystkich kierunkach. Pomiędzy typowym szkieletem osiowym a odmiennie zbudowaną czaszką możemy wyróżnić kompleks potyliczno-szczytowo-obrotowy. Dwa najwyżej leżące kręgi zostały ukształtowane odmiennie umożliwiając głowie maksymalną swobodę ruchów. W dolnej części kręgosłupa szyjnego występują kręgi o zbliżonej budowie, które funkcjonalnie mają takie same możliwości, chodź siódmy krąg różni się nieco budową anatomiczną od pozostałych. W problematyce związanej z badaniem ruchomości odcinka szyjnego kręgosłupa można odnieść się do testów klinicznych, mających charakter oceny subiektywnej oraz badań opartych na obiektywnie zebranych wynikach przy użyciu skomputeryzowanych urządzeń pomiarowych. Słowa kluczowe: kręgosłup szyjny, anatomia, zakresy ruchów, badanie ruchomości. Abstract The cervical spine is the most mobile section of the entire vertebral column. Cervical vertebrae, construct the neck skeleton, support the head allowing the appropriate orientation in all directions. Between the typical axial skeleton and differently built skull we can distinguish occipito-atlanto-axial complex. The maximum discretion of head movement is possible thanks to two highest lying vertebrae which are dissimilar shaped. In the lower part of the cervical spine are vertebrae with similar construction and functional abilities. The seventh vertebra has slightly different anatomy structure. The issues related to the examination of cervical spine range of motion can be applied to clinical tests which are subjective evaluation and research based on objectively collected results using computerized measurement devices. Key words: cervical spine, anatomy, range of motion, motion measurement.